Facile synthesis, mechanical toughening, low thermal conductivity and fire-retardant of lightweight quartz fiber reinforced polymer nanocomposites. (28th July 2021) - Xu, Jianguo; Hong, Changqing; Geng, Jun; Jin, Xiangyu; Pan, Yiwu; Wang, Hebing; Luo, Xiaoguang; Zhang, Xinghong
Abstract: Lightweight and nanoporous composite materials with excellent thermal insulation and strong mechanical property are urgently required to address prominent issues that pertain to application. The main challenge of synthesizing such materials is to reduce the thermal conductivity and improve its rigid-flexible combined property as well as its heat resistance. Here, we propose to prepare a completely lightweight 3D bulk composites by vacuum impregnation and gel polymerization processing with a needled quartz fiber felt (NQF) as the reinforcement and phenolic resin aerogel (PR) as the matrix. The nanoporous PR is facilely synthesized by polymerization-induced phase separation with phenolic resin, and the resultant nanoporous PR is uniformly filled and distributed in NQF without macroscopic cracking and agglomeration. The as-prepared NQF/PR nanocomposites possessed enhanced mechanical property with compressive strength (1.76–2.84 MPa) and Young's modulus (26.71–39.60 MPa) in the xy direction. Importantly, the NQF/PR nanocomposite was not damaged as the strain reached 50% in z direction. Compared to most organic-based aerogel and aerogel-like materials, the present NQF/PR nanocomposite aerogels exhibited excellent flame resistances with 1000 °C fire duration time exceeding 30 min and excellent thermal insulation properties with low thermal conductivities that varied from 0.017 W/m ⋅ K to 0.031 W/m ⋅ K. This experimental results show that the synthesized NQF/PR nanocomposites by this method are very suitable to heat high-performance lightweight insulation materials for industrial compatibly and production. Graphical abstract: Image 1